2023
DOI: 10.2478/nispa-2023-0002
|View full text |Cite
|
Sign up to set email alerts
|

Parental Leave Policy in European Countries: A Comparative Approach Using Cluster Analysis

Abstract: Currently, parental leave policy is one of the key instruments of social policy in the family sphere in many European countries. Despite the common territorial context, parental leave design may vary greatly in different European countries. In this respect, the influence of differentiative parameters of the parental leave system on the social policy results in European countries is still overlooked. Our study aims to compare parental leave policies in European countries using cluster analysis and reveal the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Western European countries are characterized by stricter requirements for receiving benefits during parental leave, the use of tools for combining professional and parental activities, the predominance of corporate support and social insurance for families with children (Makay, 2023). At the same time, it was revealed that the geographical principle is not the strongest in the differentiation of parental leave policies: groups of Central and Eastern Europe and Western Europe countries have quite similar statistical indicators calculated by the number of flexibility elements in different types of leave (Bagirova et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Western European countries are characterized by stricter requirements for receiving benefits during parental leave, the use of tools for combining professional and parental activities, the predominance of corporate support and social insurance for families with children (Makay, 2023). At the same time, it was revealed that the geographical principle is not the strongest in the differentiation of parental leave policies: groups of Central and Eastern Europe and Western Europe countries have quite similar statistical indicators calculated by the number of flexibility elements in different types of leave (Bagirova et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%